The Effectiveness of Digital Storytelling on Language Comprehension of Children with Autism Spectrum Disorders: A Systematic Literature Review - Kubro, Intan Khodijatul; Rachmasari, Firtha Ayu (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This systematic literature review examines the impact of digital storytelling interventions on the language comprehension skills of children diagnosed with autism spectrum disorders (ASD). Given the communication challenges faced by individuals on the autism spectrum, there is a growing interest in leveraging digital storytelling as a potential tool for language development. The review synthesizes findings from relevant studies, focusing on key components such as visual support, multimodal presentation, repetition, interactivity, personalization, and the incorporation of social narratives. The research shows promising outcomes, indicating that digital storytelling improves language comprehension in children with ASD. The review emphasizes the potential benefits along with the need for more investigation to determine the best intervention settings, treatment periods, and skill generalization. The review's conclusion deepens our understanding of how digital storytelling aids in the language development of kids with ASD and has useful ramifications for educators, researchers, and special education practitioners.